2014
DOI: 10.1016/j.adhoc.2012.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Reliable neighbor discovery for mobile ad hoc networks

Abstract: We define a reliable neighbor discovery layer for mobile adhoc networks and present two algorithms that implement this layer as a service with varying progress guarantees. Our algorithms are implemented atop an abstract MAC layer [13], which deals with the lower level details of collision detection and contention. Specifically, we first describe a basic region-based neighbor discovery protocol with weak progress guarantees. Informally speaking, this protocol does not guarantee communication links when nodes mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Gorrieri et al analyzed the performance of clustered vehicular sensor networks, and found some insights in the trade-off between decision delay and energy efficiency [12]. Cornejo et al studied a reliable neighbor discovery layer for MANETs, which could be applied in regular square region or hexagonal tiling region [13]. Han et al investigated the relay placement and power allocation for cooperative relaying [14].…”
Section: Vanets Architecture and Minimum Spanning Tree Problemmentioning
confidence: 99%
“…Gorrieri et al analyzed the performance of clustered vehicular sensor networks, and found some insights in the trade-off between decision delay and energy efficiency [12]. Cornejo et al studied a reliable neighbor discovery layer for MANETs, which could be applied in regular square region or hexagonal tiling region [13]. Han et al investigated the relay placement and power allocation for cooperative relaying [14].…”
Section: Vanets Architecture and Minimum Spanning Tree Problemmentioning
confidence: 99%
“…The determination of the direct neighboring nodes is generally done using hello protocols where each node periodically broadcasts a hello message. Each node considers another node as a direct one-hop neighbor only if it receives at least one hello message from it [33] [34]. The random access discovery schemes require the nodes to be randomly in a "listen" or "transmit" mode in each time slot so that each node receives the hello message from every neighbor at least once in a predefined time period.…”
Section: Neighbor Discovery Overheadmentioning
confidence: 99%
“…al [37] using Decay, and by [38] using Analog Network Coding. Applications of absMACs: The first to study an advanced problem using the absMAC of [41] were Cornejo et al [10,11], who investigated neighbor discovery in a mobile ad hoc network environment. Global SMB and MMB broadcast were studied by [37] in probabilistic environments and by Ghaffari et al [23] in the presence of unreliable links.…”
Section: Abstract Mac Layermentioning
confidence: 99%
“…Due to the choice of Q this is O(log α (Λ) · log(1/ε approg )). All this is executed for each of the Φ phases of an epoch (Lines [6][7][8][9][10][11][12][13][14][15]. Thus the total runtime of an epoch is…”
Section: Runtime Of An Epochmentioning
confidence: 99%